Posted by **confused** on Friday, May 25, 2007 at 3:21pm.

Given g(x) = –2x – 1, find g(3a).

G(3a)=-2(3a)-1

= -6a-1

= -5

is this right or do I just stop at -6a-1

Just stop at -6a-1

Matt

Also, let me add this.

If you have -6-1 (without the "a") that would be -7. Not -5.

But -6a-1 is the correct answer for this problem.

Matt

thank you for clearing this up for me.

:-) Glad I could help.

## Answer This Question

## Related Questions

- English - Hi we had to write a poem for english class, i was wondering if mine ...
- algebra - Given f(x) = 2x - 5, find f(-3a). F(x)= 2(-3a) -5 F(-3a) = 2(3a)-5 = 1...
- Spanish Stop-motion quote - Hey guys, I'm making a lego stop-motion movie and I ...
- french - I have questions about pronominal verbs, let say "se arreter". Je m'...
- Algebra - Evaluate the given function for the value specified. 2. f(x) = x ...
- Physics - If a young girl is in a truck that is rolling down a hill with a force...
- algebra - 1 1 7 -y - -= - 2 8 8 please help me! It isn't clear to me what this ...
- world issues- amazon deforestation - Hi. I was assigned an essay that I have to ...
- Physics - A disk in your computer spins at 5400 rpm. If this disk turns through ...
- Algebra 2 - Helllo I have no idea how to do this problem given f(x) = x-3(x + 4...

More Related Questions